Low‐temperature selective laser sintering 3D printing of PEEK‐Nylon blends: Impact of thermal post‐processing on mechanical properties and thermal stability. Issue 23 (25th February 2022) - Chavez, Luis A.; Ibave, Paulina; Hassan, Md Sahid; Hall‐Sanchez, Samuel E.; Billah, Kazi Md Masum; Leyva, Alba; Marquez, Cory; Espalin, David; Torres, Sabrina; Robison, Thomas; Lin, Yirong
Abstract: A high‐performance polymer (HPP) (polyether ether ketone, PEEK) blended with a commercial low‐temperature polymer (polyamide 12, PA‐12) was fabricated using a low‐temperature selective laser sintering (SLS) 3D printer. Different post‐processing heat treatments were implemented after fabrication to tune the thermal and mechanical properties of printed blends. The specific mechanical modulus of the blend was increased up to 79% in comparison to printed PA‐12 samples with heat treatment. Additionally, the thermal resistance of the treated blends greatly exceeded the properties observed using PA‐12 alone. This research proposes a methodology to fabricate and engineer HPP using desktop SLS printers through a secondary lower melting temperature material and heat treatments. Abstract :